Considerations and implications in shade selection for dental restorations: A review - Malik Abdulaziz Alayed (Wolters Kluwer Medknow Publications, 2021)
Newer trends in shade matching have been driven by the market need for superior grade esthetic restorations. Modernized shade guides, obtainability of shade-taking devices, and research in the field of human color vision have ameliorated the capability of dentists to attain outstanding color-matched restorations. A detailed knowledge of natural teeth' appearance features is needed along with these new devices to increase shade-matching results.